Pemeriksaan Kadar Hemoglobin dan Pemberian Edukasi tentang Anemia pada Remaja Putri - Karinda, Merlin; Muflihah, Muflihah; Vaira, Rizky (UKInstitute, 2022)
Anemia is still a public health problem in Indonesia that needs special attention. Based on the 2018 Riskesdas, the prevalence of anemia in adolescents is 32%, meaning that 3-4 out of 10 adolescents suffer from anemia. This is influenced by the habit of nutritional intake that is not optimal and lack of physical activity. The impact of anemia on adolescent girls and poor nutritional status have a negative contribution when pregnant in adolescence or adulthood which can lead to the birth of babies with low birth weight, morbidity and even death for mothers and babies. This community service aims to increase the knowledge of young women about anemia and the risks to reproductive health through the provision of health education about adolescent anemia and reproductive health as well as examination of hemoglobin levels. This community service is carried out by the method of providing health education and direct examination of hemoglobin levels to students in class XI and XII at SMA PGRI 2 Banjarmasin, totaling 75 students. Service activities like this can be carried out routinely both in the same location or in different locations with the target community really in need of health services, especially regarding anemia in adolescents. Abstrak: Anemia masih menjadi masalah kesehatan masyarakat di Indonesia yang perlu mendapat perhatian khusus. Berdasarkan Riskesdas 2018 prevalensi anemia pada remaja sebesar 32%, artinya 3-4 dari 10 remaja menderita anemia. Hal tersebut dipengaruhi oleh kebiasaan asupan gizi yang tidak optimal dan kurangnya aktifitas fisik. Dampak anemia pada remaja putri dan status gizi yang buruk memberikan kontribusi negatif bila hamil pada usia remaja ataupun saat dewasa yang dapat menyebabkan kelahiran bayi dengan berat badan lahir rendah, kesakitan bahkan kematian pada ibu dan bayi. Pengabdian masyarakat ini bertujuan untuk meningkatan pengetahuan remaja putri tentang anemia dan resiko terhadap kesehatan reproduksi melalui pemberian pendidikan kesehatan tentang anemia remaja dan kesehatan reproduksi serta pemeriksaan kadar hemoglobin. Pengabdian masyarakat ini dilakukan dengan metode pemberian pendidikan kesehatan serta pemeriksaan langsung kadar haemoglobin kepada siswi kelas XI dan XII di SMA PGRI 2 Banjarmasin yang berjumlah 75 orang siswi. Kegiatan pengabdian seperti ini dapat dilakukan secara rutin baik di lokasi yang sama maupun di lokasi yang berbeda dengan sasaran masyarakat yang benar-benar membutuhkan pelayanan kesehatan terutama mengenai anemia pada remaja.